Sour cherry as a functional food - Homoki, Judit; Nemes, Andrea; Remenyik, Judit (Acta Agraria Debreceniensis, 2014)
The antioxidant capacity of ’Debreceni bőtermő’, ’Újfehértói fürtös’ and ’Érdi bőtermő’ cultivars were determined by FRAP (Ferric Reducing Ability of Plasma), DPPH (1,1-diphenyl-2-picrylhydrazyl radical-scavenging activity) and photochemiluminescence method. In sour cherry, the most antioxidant effects of natural bioactive compounds are anthocyanins. Our results show that the photochemiluminescence method out of applied assays is ratheris suitable to determine the antioxidant capacity of red soft fruits and tart cherries. The correlation is good between the determined anthocyanin concent by this technic and pH-differential spectrophotometry. However, both FRAP and DPPH assays are inaccurate.The anthocyanin composition of ’Debreceni bőtermő’, ’Újfehértói fürtös’ and ’Érdi bőtermő’ ’Csengődi csokros’ sour cherry varieties were analised. There are big differences between the accumulation of anthocyanan compounds of cultivars. ’Csengődi csokros’ produce melatonin in large quantity. On the evidence of the results, we can say that the hungarian sour cherry cultivars are suitable for functional food development.